Cephalometric predictors of abnormal sella turcica among individuals with Sheehan Syndrome: A case-control study (Research, Society and Development, 2021)
The present study aimed to analyze cephalometric predictors of abnormal sella turcica (ST) in Sheehan Syndrome (SS) patients. An observational case-control study was performed with SS volunteers from the Endocrinology and Diabetology Service of the Walter Cantídio University Hospital (Brazil). The sample was composed of 32 patients allocated in two groups: case group (16 adult women diagnosed with SS) and control group (16 healthy individuals matched by sex and age). Analyzes of the linear dimensions (length, diameter, and depth) of the ST on lateral teleradiographies were made using the Radiocef Studio 2 software. The morphological pattern (anterior oblique wall, double floor contour, bridged, irregularities of the dorsal face, pyramidal) was also assessed. The subjects mean age was 65.47 ± 10.19 years. SS patients had lower mean length (p